Estudio fenológico de la línea promisoria de amaranto (Amaranthus spp.) UTC 008 en dos localidades, parroquia Tigualo y Laigua De Maldonado provincia de Cotopaxi. 2020. - Pilatasig Chiluisa, Edgar Iván (2020)
The research aimed to describe the phenological stages of the promising line of amaranth cultivation (Amaranthus spp.) UTC 008 in two locations, Tigualo parish and Laigua De Maldonado, Cotopaxi province. In the course of the research the different phenological stages of the crop were studied: emergency, vegetative phase, reproductive phase, physiological maturity in each of the phenological stages was recorded the days elapsed, also recorded the plant height from the base of the stem to the apical meristema averaging a data per month. For the interpretation of data was based on the phenological stages showing the following data in both locations: locality 1 emergency stage 17 days and locality 2 in 15 days; vegetative phase locality 1 in 46 days and locality 2 in 41 days; reproductive phase locality 1 in 107 days and locality 2 in 95 days and finally physiological maturity locality 1 in 159 days and locality 2 in 154 days. On the other hand, the floor height was indicated in both locations, in the first month there was equality of 3 cm, in the second month the town 1 with 26 cm and the town 2 with 24 cm, in the third month the town 1 with 102 cm and the town 2 with 97 cm, in the fourth month the town 1 with 148 cm and locality 2 with 147 cm, its heights began to take similarity , and finally in the fifth month showed that in both locations they reached a height of 150 cm. This research will provide farmers with good agronomic management and obtain sustainable production.